Monetary policy and financial market stability: does inflation targeting make a difference? - Merafe, Itumeleng (My University, 2016)
Since the early 1990s an increasing number of countries are adopting inflation targeting and although it has been lauded as a successful monetary policy regime this paper seeks to determine whether or not inflation targeting is sufficient to bring about financial market stability. We compare 10 emerging market economies, 6 that have adopted inflation targeting and 4 that have not in order to ascertain whether or not there is a significant difference between these groups of countries based on 2 financial market stability indicators, the first being the volatility of equity markets and the second being currency volatility. From these results, there is no evidence that inflation targeting has had any impact on the stability of financial markets and in some instances, non-targeters have outperformed targeters in terms of the improvements in stability
Masters in Management: Finance and Investment, Wits Business School
Keywords: Economic development--Malawi; Democracy--Malawi